1959
DOI: 10.1002/path.1700780121
|View full text |Cite
|
Sign up to set email alerts
|

The indirect action of subcutaneous injections of glycerol on the renal tubules in the rat

Abstract: A PREVIOUS paper (Pinckh, 1957) recorded the successive histopathological changes in the rat's kidney after subcutaneous injection of glycerol. It was shown that such injections were quickly foliowed by severe haemoglobinaemia, haemoglobinuria and degeneration and necrosis of the renal tubules (" acute tubular nephrosis "). The latter resembled the condition of the same name occurring in man.The object of the experiments now to be described was to determine whether the glycerol acted directly on the renal tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1960
1960
1977
1977

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…The mean pressure in 51 proximal tubules of ten dehydrated control rats was 15.0 + 0.2 cm HO, a pressure slightly less than that of nondehydrated control rats, significant at the 5% confidence limit (Figure 3). Fifteen (31)(32)(33)(34)(35)(36)(37)(38). The histologic lesions produced in this manner have been well described, and seem to be consistent from study to study.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The mean pressure in 51 proximal tubules of ten dehydrated control rats was 15.0 + 0.2 cm HO, a pressure slightly less than that of nondehydrated control rats, significant at the 5% confidence limit (Figure 3). Fifteen (31)(32)(33)(34)(35)(36)(37)(38). The histologic lesions produced in this manner have been well described, and seem to be consistent from study to study.…”
Section: Resultssupporting
confidence: 58%
“…The histologic lesions produced in this manner have been well described, and seem to be consistent from study to study. In appearance, distribution, and reversibility they closely resemble the lesions seen in the kidney of man with acute renal failure due to transfusion accidents or crush injury (33).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Glycerol is not toxic per se (Finck, 1959;Mason, Alexander & Teschan, 1963). Finck (1959Finck ( , 1965 attributed renal insufficiency to a number of vascular mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…He found that intraperitoneally administered glycerol failed to produce hemoglobinuria, yet it evoked a renal lesion identical histologically to that after glycerol injection by the subcutaneous or intramuscular routes. This question remains unresolved, however, since Carroll, Kovacs, and Tapp (14), using a larger dose of glycerol than that given by Finckh (13), did note hemoglobinuria associated with the renal lesion that followed intraperitoneal injection of glycerol. In any event, the lesion after glycerol injection appears to resemble morphologically that produced by nephrotoxic substances (15), and Oken and his co-workers have noted identical functional changes in that lesion and the one produced by mercury in the rat (1, 2).…”
Section: Discussionmentioning
confidence: 99%